Influence of Hydrogen Peroxide on the Bleaching Process of Pulp Derived from Oil Palm Fronds and Empty Fruit Bunches - Hariani, Razita; Asma Deli, Nur; Dhora, Anna (Journal of Engineering Science and Technology Management, 2025)
Oil palm fronds and empty fruit bunches (EFB) are the main by-products of oil palm plantations. Typically, these residues are used for organic fertilizer, mat production, or as a growing medium for plants and fungi. However, oil palm fronds and EFB have high cellulose content, making them promising raw materials for pulp and paper production. This study aimed to investigate the pulp and papermaking process using oil palm fronds and EFB as raw materials. A soda pulping process was applied, followed by bleaching using various concentrations of hydrogen peroxide, namely 8%, 10%, 12%, 14%, and 16%. The results showed that optimal pulp and paper quality was achieved using 16% hydrogen peroxide, which produced pulp with a brighter and whiter appearance. The resulting paper showed a thickness of 0.62 mm, a grammage of 56.58 g/m², and a density of 35.07 kg/m³.